Low NAD+ Levels Are Associated With a Decline of Spermatogenesis in Transgenic ANDY and Aging Mice - Meyer-Ficca, Mirella L.; Zwerdling, Alexie E.; Swanson, Corey A.; Tucker, Abby G.; Lopez, Sierra A.; Wandersee, Miles K.; Warner, Gina M.; Thompson, Katie L.; Chini, Claudia C.S.; Chen, Haolin; Chini, Eduardo N.; Meyer, Ralph G. (Frontiers in Endocrinology, 2022)
Advanced paternal age has increasingly been recognized as a risk factor for male fertility and progeny health. While underlying causes are not well understood, aging is associated with a continuous decline of blood and tissue NAD+ levels, as well as a decline of testicular functions. The important basic question to what extent ageing-related NAD+ decline is functionally linked to decreased male fertility has been difficult to address due to the pleiotropic effects of aging, and the lack of a suitable animal model in which NAD+ levels can be lowered experimentally in chronologically young adult males. Using a novel transgenic mouse model, this report demonstrates for the first time that decreasing testicular NAD+ levels in young adult mice, to levels that match or exceed the NAD+ decline observed in old mice, results in the disruption of spermatogenesis with small testis sizes and reduced sperm counts. In this mouse model of acquired niacin dependency (ANDY), transgenic mice are dependent on dietary vitamin B3 (niacin) for NAD+ synthesis, similar to humans. These mice develop NAD+-deficiency on a niacin-free diet, which is reversed by niacin supplementation. Providing niacin to NAD+-depleted ANDY mice fully rescued spermatogenesis and restored normal testis weight in the animals. The results suggest that NAD+ is important for proper spermatogenesis and that its declining levels during aging are functionally linked to declining spermatogenesis and male fertility. Functions of NAD+ in retinoic acid synthesis, which is an essential testicular signaling pathway regulating spermatogonial proliferation and differentiation, may offer a plausible mechanism for the declining spermatogenesis observed in NAD+-deficient mice.